Court doctors in Modern Europe: Cesare Macchiati (1629-1675) a doctor travelling with Queen Christina of Sweden - Zurlini, Fabiola; Iorio, Silvia; Nigrisoli Wärnhjelm, Vera (Medicina Historica, 2024)
Background and aim: Court doctors have long been a neglected topic for medical historians as they often represent minor figures with a little editorial production at a scientific level, more relevant for the political and diplomatic role played at court rather than for their medical one. Only recently, medical historians have understood their importance, starting to investigate the relationship between court medicine and the medical context of the society of the time. Among these still little-known figures, to whom historiography is paying attention, there is Cesare Macchiati (1629-1675), a doctor at the Roman court of Queen Christina of Sweden from 1659 to 1675. Materials and Methods: As a court doctor, Macchiati joined the Queen on two journeys to Northern Europe, towards Sweden, respectively between 1660 and 1668, leaving about fifty letters, addressed to Cardinal Decio Azzolino Jr, as a documentation of these journeys. Results: From the study of these letters, it is possible to deduce some biographical information on court medical practice, the queen’s temperament and illnesses and the circulation of a new medical knowledge at the court, which was favoured by the journey. Conclusions: The biography highlights how the role of a court doctor, which was consolidated by the experience of the journey to Europe in Macchiati’s case, becomes a prerequisite for a professional rise on his return to Rome in the most important city medical institutions, such as the university, the Roman medical college at the pontifical curia, characterized by a cosmopolitan context thanks to the international professional background, developed at the Queen’s court.